2019
DOI: 10.1002/aenm.201901612
|View full text |Cite
|
Sign up to set email alerts
|

Direct Nanoscale Characterization of Deep Levels in AgCuInGaSe2 Using Electron Energy‐Loss Spectroscopy in the Scanning Transmission Electron Microscope

Abstract: A new experimental framework for the characterization of defects in semiconductors is demonstrated. Through the direct, energy‐resolved correlation of three analytical techniques spanning six orders of magnitude in spatial resolution, a critical mid‐bandgap electronic trap level (EV + 0.56 eV) within Ag0.2Cu0.8In1−xGaxSe2 is traced to its nanoscale physical location and chemical source. This is achieved through a stepwise, site‐specific correlated characterization workflow consisting of device‐scale (≈1 mm2) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…600 meV: regularly observed for different measurement parameters, but sometimes difficult to evaluate. Similar results are reported in literature [11,13].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…600 meV: regularly observed for different measurement parameters, but sometimes difficult to evaluate. Similar results are reported in literature [11,13].…”
Section: Discussionsupporting
confidence: 93%
“…They investigated the effect of RbF as well, and observed no reduction of the density of this trap, supporting the present results. Deitz et al show measurements of a 560 meV trap in a silver alloy of CIGS (Ag, Cu)(In, Ga)Se 2 (ACIGS) as well and assigned it to the Cu In/Ga substitutional defects as the most likely source [13]. Ab initio DFT calculations by Zhang et al yield a trap energy of 580 meV for Cu In traps in CuInSe 2 (CIS) which confirms this assignment even more.…”
mentioning
confidence: 89%
“…The lowering of the midgap trap concentration upon annealing is consistent with the increase in measured lifetime by TRPL after dark heat exposure (vide infra) and is likely associated with reduced atomic disorder from annealing, leading to a reduction of Cu M (M = Ga or In) substitutional defects. 26 The observed reduction in V oc with DH1000, which we attribute to a decrease in carrier concentration, occurs despite this reduction in midgap defects.…”
Section: Journal Of Applied Physicsmentioning
confidence: 77%
“…As well as establishing the expected compositional depence of the band gap, these analyses may allow further correlations, such as possible band gap polymorphism depence [ 62 ]. Additionally, recent studies have shown the potential of the technique for the analyses of atomic defects in semiconductors, being able to detect and characterize sub-bandgap defect levels, which are key in the later performance of the material [ 66 ].…”
Section: Spectroscopy In Stemmentioning
confidence: 99%